VALUE CREATION AND CAPTURE IN BUYER-SUPPLIER RELATIONSHIPS: A NEW PERSPECTIVE - Fábio Campos Tescari; Luiz Artur Ledur Brito (RAE: Revista de Administração de Empresas, 2016)
This research paper develops and tests a new model for value creation and capture in buyer-supplier relationships. In addition to including both value creation and capture in the same model, value creation is unraveled by the identification of its sources, both intrinsic and relational. Intrinsic value is the set of benefits derived from resources belonging to one party that can be captured by another party if there is a relationship between them, even if this relationship is non-collaborative. Relational value encompasses the mutual benefits that are generated as the collaboration between buyer and supplier increases. The model was tested using a survey of 127 dyads (buyer and supplier). The results indicated that both sides benefit from the total value created by the relationship, but the degree of value capture varies. The value perceived by the supplier is greater than that perceived by the buyer, which consequently encourages the former to boost its efforts even further to ensure that the relationship continues.